Further studies on Mesopotamian witchcraft beliefs and literature - Abusch, I. Tzvi, (Ancient Magic and Divination;, 2020)
"Among the most important sources for understanding the cultures, religions, and systems of thought of ancient Mesopotamia is the large corpus of magical and medical texts directed against witchcraft. The most important of these texts is the Akkadian series Maqlû ("Burning"). This volume offers a collection of studies on Mesopotamian witchcraft and Maqlû written subsequent to the appearance of the author's 2002 collection of studies on witchcraft (Brill, 2002). Many of the studies reprinted here take a diachronic approach to individual incantations and rituals and attempt to solve textual difficulties using literary-critical and/or text-critical approaches".